Hubungan Antara Tipe Kepribadian, Bauran Pemasaran Jasa dan Niat Membeli Ulang - Deri Rachmat Rizki; Achsania Hendratmi (Universitas Airlangga, 2017)
This research aims to know the influence of personality types against perception, perception of services marketing mix the marketing mix of services against the intention to buy back products fashions in Rabbani and personality types against the intention to buy back products fashions at Rabbani. The subject of this research is the intention to buy back products fashions at Rabbani. The type of the data being used is the primary data with 149 correspondents. This research method using quantitative methods with technical analysis path. The results showed that the personality types have no effect significantly to perceptions of service marketing mix. However, the perception of service marketing mix positive significant effect against the intention of buying it back. And personality type back has no effect against the intention of buying it back.